Getting on Board Involving Directors in Leader Development - Neisendorf, Barbara; Neisendorf, Barbara; Saslow, Scott (Center for Creative Leadership, 2006)
In addressing the many challenges of running a high-impact executive development program, organizations can now enlist the support of a powerful ally that has a vested interest in a strong executive cadre: the board of directors.